2017
DOI: 10.1038/gim.2017.9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the feasibility of delivering standardized genomic care using ophthalmology as an example

Abstract: word count: 198 2 ABSTRACT Purpose:Broadening access to genomic testing and counselling will be necessary to realise the benefits of personalised healthcare. This study aimed to assess the feasibility of delivering a standardised genomic care model for inherited retinal dystrophy (IRD) and of using selected measures to quantify its impact on patients. Methods:A pre-post prospective cohort study recruited 98 patients affected by IRD to receive standardised multidisciplinary care. A checklist was used to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 32 publications
0
25
0
2
Order By: Relevance
“…The role of genetics or genomics specialists was described in eight papers. 8,22,24,30,31,34,52,53 Five 8,22,24,31,32 reported that clinicians had variable or limited access to genetics services and reported having 'unfamiliar' relationships with geneticists. 32 The lack of genetics expertise across the workforce was identified as a barrier to patient referral to genetic services in a systematic review.…”
Section: Genetics/genomics Specialistsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of genetics or genomics specialists was described in eight papers. 8,22,24,30,31,34,52,53 Five 8,22,24,31,32 reported that clinicians had variable or limited access to genetics services and reported having 'unfamiliar' relationships with geneticists. 32 The lack of genetics expertise across the workforce was identified as a barrier to patient referral to genetic services in a systematic review.…”
Section: Genetics/genomics Specialistsmentioning
confidence: 99%
“…31 Three described use of multi-disciplinary teams (MDTs) to deliver specialised genetics services. 30,52,53 Evaluation of an American paediatric telemedicine service demonstrated a positive impact on patients who reported high satisfaction, especially in underserved areas, because of the model's flexibility and decrease in waiting times. 30 Members of a rare disease MDT in the UK described how they valued the clinical and scientific diversity to make informed decisions about eligibility for GS, though it was acknowledged the MDT was resource intensive and, beyond certain conditions, remains unusual in UK health services.…”
Section: Genetics/genomics Specialistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar dessa definição ainda não ser formalizada, o empoderamento ganhou destaque nos serviços de saúde (WALLERSTEIN, 2006;HERBERT et al, 2009) COSTAL TIRADO et al, 2017;DAVISON et al, 2017;PALMER et al, 2018;ISON et al, 2019).…”
Section: Empoderamento Como Um Referencial Para O Aconselhamento Genéunclassified
“…Dinamarca, Espanha e Holanda (DINESS et al, 2017;MUÑOZ-CABELLO et al, 2017;VOORWINDEN et al, 2019). Além disso, foi utilizada como instrumento para avaliar o AG em diversos serviços de aconselhamento genético (INGLIS et al, 2015;COSTAL TIRADO et al, 2017;DAVISON et al, 2017;PALMER et al, 2018;ISON et al, 2019).…”
Section: Genetic Counseling Outcome Scale: No Mundounclassified